IMPLEMENTING INTEGRATED FORMAT IN ASSESSING READING COMPREHENSION: A CASE OF VIETNAMESE EFL LEARNERS - Thanh, Trinh Ngoc (VNU Journal of Foreign Studies; Vol 37 No 1DO - 10.25073/2525-2445/vnufs.4660, 2021)
The present study evaluates the effect of test format on the performance of reading comprehension, which is the integrated format. Unlike the separation of text and test questions into two sections in the split format, the main modification of the integrated format is that the relevant text is integrated with test questions in each reading task. Through the comparison between learners’ performance in the two test formats, this study tests the hypothesis that the overall test performance and task performance in the integrated format are higher than performance in the split format. Drawn on score data of 20 Vietnamese EFL learners, findings from the study showed no effect of test format on the overall test performance and marginally significant effect of test format on task performance. A further analysis on relevant aspects of test design is to be discussed .